Effect of Guano and Liquid Organic Azolla pinnata Fertilization on the Growth of Pakcoy (Brassica rapa L.) - Indarwati Indarwati; Mochamad Thohiron; Sukian Wilujeng; Medita Johana Pakula Bafiqi; Rochmad Zulfikar (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2026)
This study aimed to evaluate the effects of varying doses of Guano fertilizer and concentrations of liquid organic fertilizer (LOF) derived from Azolla pinnata on the growth and yield of pakcoy (Brassica rapa L.). The experiment was conducted using a Randomized Complete Block Design (RCBD) with two factors and three replications. The first factor was the Guano fertilizer dose, consisting of four levels: 0 g (A0), 20 g (A1), 40 g (A2), and 60 g (A3). The second factor was the concentration of Azolla pinnata LOF, also with four levels: 0 ml/L (B0), 15 ml/L (B1), 30 ml/L (B2), and 45 ml/L (B3). Observed parameters included plant height, number of leaves, root length, fresh weight, and dry weight. Treatment with 60 g Guano (A3) had the most positive effect on several growth indicators, such as plant height and leaf number. Meanwhile, the 30 ml/L concentration of Azolla LOF (B2) also contributed significantly to growth parameters. The combination of 60 g Guano and 30 ml/L Azolla pinnata LOF (A3B2) proved to be the most effective in enhancing pakcoy growth, producing the highest fresh weight of 190 g per plant. Keywords: Plant Growth, Pakcoy, Guano Fertilizer, Liquid Organic Fertilizer